PENDIDIKAN AKHLAK ANAK PANTI ASUHAN DI KABUPATEN TAPIN - Mahfuz, Ahmad (AL-FALAH: Jurnal Keislaman dan Kemasyarakatan, 2025)
Children need to be educated as fully as possible, so that they become complete individuals, so that moral education in children is a guide that is in accordance with the teachings of the Islamic religion so that children become perfect human beings. Moral education for children in orphanages is non-formal education which also applies moral education, especially as children can be supervised in their daily lives because they are in an orphanage environment. The purpose of this research is that researchers want to know the moral education of children in orphanages in Tapin Regency. This can be seen from the point of view of the objectives of moral education, educators or caregivers, students or foster children, moral education materials or materials for foster children, moral education methods and the moral education environment. The research was carried out at 4 orphanages in Tapin Regency by looking at each sub-district representative, namely Budi Akhlakul Karimah, Siti Khadijah, Miftahussalam and Izzul Hasan Orphanages.The results of national research illustrate that the objectives of moral education for children in orphanages in Tapin Regency are in accordance with educational objectives. Then the educator, who is meant as a caregiver for orphanage children, has a role as a teacher in guiding daily moral education. Then, in research studies, the material for moral education is about honesty, tolerance and courtesy. The caregiver's method of moral education is taught by example and habituation. This exemplary and habituation method can also be combined with other methods such as emotional, functional and rational experiences. However, the advice method is the mainstay method for every caregiver. Keywords: Moral Education, Moral Education Orphanage Children, Orphanage Children, The Moral Environment Of Orphanage Children.                     Anak perlu dididik semaksimal mungkin, supaya menjadi pribadi yang utuh, sehingga pendidikan akhlak pada anak adalah sebuah tuntunan yang sesuai ajaran agama islam agar anak menjadi insan yang sempurna. Pendidikan akhlak pada anak panti asuhan yang merupakan pendidikan nonformal yang juga menerapkan pendidikan akhlak, terlebih keseharian anak dapat di awasi karena dalam lingkungan panti asuhan. Tujuan dilakukannya penelitian ini ialah peneliti ingin mengetahui pendidikan akhlak anak panti asuhan yang ada di Kabupaten Tapin. Hal ini dapat dilihat berdasarkan sudut pandang tujuan pendidikan akhalaknya, pendidik atau pengasuh, peserta didik atau anak asuh, materi atau bahan pendidikan akhlak anak asuh, metode pendidikan akhlak serta lingkungan pendidikan akhlak. Penelitian dilaksanakan pada 4 Panti asuhan yang ada di Kabupaten Tapin dengan melihat pada masing-masing perwakilan kecamatan yaitu Panti asuhan Budi Akhlakul Karimah, Siti Khadijah, Miftahussalam dan Izzul Hasan. Adapun hasil penelitian menggambarkan bahwa Tujuan pendidikan akhlak anak panti asuhan di Kabupaten Tapin sudah sesuai dengan tujuan pendidikan nasional. Kemudian pendidik yang dimaksud pengasuh anak panti memiliki peran sebagai guru dalam membimbing pendidikan akhlak sehari-hari. kemudian dalam kajian penelitian yang menjadi materi pendidikan akhlak adalah tentang jujur, toleransi dan sopan santun. Adapun metode pengasuh dalam pendidikan akhlak tersebut diajarkan dengan metode keteladanan dan pembiasaan. Metode keteladanan dan pembiasaan tersebut, bisa juga dikombinasikan dengan metode yang lain seperti emosional, fungsional pengalaman dan rasional,. Namun, metode nasihat merupakan metode andalan setiap pengasuh. Kata Kunci: Anak Panti Asuhan, Lingkungan Akhlak Anak Panti Asuhan, Pendidikan Akhlak, Pendidikan Akhlak Anak Panti Asuhan.